DEVELOPMENT OF HISTORICAL LEARNING E-MODULE BASED VALUE CLARIFICATION TECHNIQUE (VCT) - Riza Umami; Nurul Umamah; Sumardi Sumardi; Riza Afita Surya (JURNAL HISTORICA, 2021)
Learning history in 21st century requires students to have 4C skills, master technology and have superior character. The purpose of this research is to produce a validated product in the form of an E-module based on Value Clarification Technique (VCT). The research and development procedure was carried out using the R2D2 model development. The R2D2 model consists of 4 phases, namely: (1) Identify a Values Issue; (2) Group members engage; (3) Encourage Seven Valuing Procesess; and (4) Create an Atmosphere of Safety, Respect and Nonimpostition Values. The results of the material content expert test reached 88% with "very good" qualifications, the learning design expert validation reached 83,33% with "good" qualifications and 76% of language validation with "good" qualifications. The benefit of this research is related to E-module based on Value Clarification Technique (VCT).